Combinatorial Efficacy and Toxicity of an Engineered Toxin Body MT-3724 with Gemcitabine and Oxaliplatin in Relapsed or Refractory Diffuse Large B Cell Lymphoma. (16th March 2023) - Lin, Chenyu; Galal, Ahmed; Rizzieri, David; Chawla, Sant; Lee, Seung T.; Georgy, Angela; Dabovic, Kristina; Strack, Thomas; McKinney, Matthew
Abstract: MT-3724 is an engineered direct-kill immunotoxin comprised of a CD20-specific scFv fused to a Shiga-like toxin subunit. In this phase IIa study, eight patients with relapsed diffuse large B-cell lymphoma were treated with MT-3724 combined with gemcitabine and oxaliplatin (GEMOX). The objective response rate was 85.7%, with a median duration of response of 2.2 months. The 12-month overall survival and progression-free survival were 71.4% and 28.6%, respectively. Two patients experienced grade 2 capillary leak syndrome (CLS). Combination therapy with MT-3724 and GEMOX demonstrated an early efficacy signal but was limited by the incidence of CLS.